Peran Kepemimpinan Spiritual dan Spiritualitas di Tempat Kerja dalam Meningkatkan Motivasi Pemimpin Kamar di Pesantren - Rizki Hidayaturrochman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the influence of spiritual leadership and workplace spirituality on the motivation of room leaders at Salafiyah Syafi’iyah Islamic Boarding School, Sukorejo Situbondo. As an Islamic educational institution emphasizing moral and spiritual values, the pesantren faces challenges in maintaining the motivation of room leaders who play a strategic role in guiding students. Spiritual leadership is believed to foster meaning and inspiration through vision, altruistic love, and faith in spiritual values within daily responsibilities. Meanwhile, workplace spirituality helps create a meaningful, harmonious, and value-based work environment aligned with Islamic principles. This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0. The sample consisted of 144 room leaders selected from a population of 226 using the Slovin formula. The instruments were adapted from Fry (2003) and Ashmos & Duchon (2000) for measuring spiritual leadership and workplace spirituality, and from Herzberg (1959) for measuring motivation. The results revealed that spiritual leadership (β = 0.492; p < 0.001) and workplace spirituality (β = 0.342; p < 0.001) both had a positive and significant effect on motivation. These findings highlight the importance of spirituality-based leadership and value-driven work environments in enhancing individual motivation within Islamic boarding schools.